Microsoft Excel 2016 : step by step - Frye, Curtis, 1968- (Redmond, Washington : Microsoft Press, a division of Microsoft Corporation, 2015)
"This is learning made easy. Gt more done quickly with Excel 2016. Jump in wherever you need answers--brisk lessons and full-color screenshots show you exactly what to do, step by step, "--Page 4 of cover.
Part 1 : Create and format workbooks. Set up a workbook ; Work with data and Excel tables ; Perform calculations on data ; Change workbook appearance -- Part 2 : Analyze and present data. Manage worksheet data ; Reorder and summarize data ; Combine data from multiple sources ; Analyze alternative data sets ; Create charts and graphics ; Create dynamic worksheets using PivotTables -- Part 3 : Collaborate and share in Excel. Print worksheets and charts ; Automate repetitive tasks by using macros ; Work with other Microsoft Office apps ; Collaborate with colleagues -- Part 4 : Perform advanced analysis. Perform business intelligence analysis ; Create forecasts and visualizations.
Includes index.
Keywords: Microsoft Excel (Computer file); Microsoft Excel (Computer file); Business -- Computer programs; Electronic spreadsheets; COMPUTERS -- Desktop Applications -- Spreadsheets; Business -- Computer programs; Electronic spreadsheets